2020
DOI: 10.3390/ijerph17113969
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Job Content and Physical Activity on Body Mass Index among Obese Managers of the Mexican Manufacturing Industry

Abstract: Mental health disorders resulting from work stressors are increasing in the Mexican manufacturing industry and worldwide. Managerial positions in these contexts are highly stressful, and although physical activity may reduce the negative effects of work stress, the relationships between these two aspects regarding their effects on the body mass index (BMI) of obese managers are scarcely studied. This article aims to study such relationships by using the Job Content Questionnaire (JCQ) dimensions with the Baeck… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…However, Netterstrom et al (1991), Hellerstedt and Jeffery (1997), Ostry et al (2006), Brunner et al (2007), Li et al (2007), Niskanen et al (2017), Muniz et al (2019), andSilva et al (2021) identified that job strain, as well as job dimensions, were associated with poor BMI. In contrast, Pelfrene et al (2002) and Armenta-Hernandez et al (2020; observed that the job dimensions were related to a reduction in BMI. Finally, five studies assessed obesity through WC.…”
Section: Additional Outcomesmentioning
confidence: 86%
See 1 more Smart Citation
“…However, Netterstrom et al (1991), Hellerstedt and Jeffery (1997), Ostry et al (2006), Brunner et al (2007), Li et al (2007), Niskanen et al (2017), Muniz et al (2019), andSilva et al (2021) identified that job strain, as well as job dimensions, were associated with poor BMI. In contrast, Pelfrene et al (2002) and Armenta-Hernandez et al (2020; observed that the job dimensions were related to a reduction in BMI. Finally, five studies assessed obesity through WC.…”
Section: Additional Outcomesmentioning
confidence: 86%
“…Regarding the risk of bias assessment of the studies considered in this study, thirty-three were classified as having a low risk of bias, while only nine were divided between moderate and high risk (Table 2 and 3). The main reasons for classifying the Netterstrom et al (1991), Kang et al (2004), Cho et al (2005), Evolahti (2012), Berset et al (2011), Magnavita andFineli (2014), Muniz et al (2019), andArmenta-Hernandez et al (2020; studies in moderate or high risk of bias were mainly due to the sample selection, definition and analysis comparability process, and analysis outcome. In the first case, the authors did not detail the participants' inclusion/exclusion criteria, in the second, there was no clarity regarding consideration of important confounding and effect-modifying factors in the data analyses, and in the last, there was no evaluation of the impact of the follow-up losses.…”
Section: Risk Of Biasmentioning
confidence: 99%
“…These authors found that the model for managers featuring normal weight has a larger explanatory power than the models developed with overweight and obese employees. Recently, another study ( Armenta-Hernandez et al, 2020 ) found that both BS and physical activity are factors that have a direct effect on the BMI of obese managers, and their research is currently conducting examinations in search for more explicative models. For instance, it was found that PE is related to normal weight because when employees feel efficient at work, they worry about their health, take care of their physical appearance, and even improve their relationships at work ( Eberly and Feldman, 2010 ).…”
Section: Theoretical Framework: Relationships Among Bs Dimensions Andmentioning
confidence: 99%
“…Such level of growth in the maquiladora industry has entailed high mental job demands and highly stressful work environments, which can increase the incidence of the BS among employees. Managers in the maquiladora industry regularly work long shifts in sedentary work conditions, which force them to adopt straining postures ( Valadez-Torres et al, 2017 ; Armenta-Hernandez et al, 2020 ). Furthermore, the maquiladoras ’ multicultural work environment places considerable mental burdens on them and demands additional job skills for which employees’ mental resources may be insufficient, all this resulting in BS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation